Cultural and Political Factors of Patterns of Personality of Civil Servants in Interwar Poland and Their Implications for Management in Public Administration - Górski , Piotr (Studia Oeconomica Posnaniensia, 2016)
This paper indicates the cultural and political factors of patterns of personality of civil servants in interwar Poland. The reason for research into patterns of personality in management is their role in the socialization process, their relationship with organizational culture, and organizational changes. The sources of empirical data was two magazines, Gazeta Administracji Państwowej (State Administration Newspaper) and Clerical Life Życie Urzędnicze. The analysis of two patterns of personality of civil servants in interwar periods in Poland shows the conditions of these patterns, as well as their influences for the relationship between civil servants and authorities of the Ministry of Internal Affairs in this period.